Evaluation of Mortality Magnitude among Holstein Friesian Calves and its Risk Factors Evaluation in an Organized Farm of Quetta Pakistan - Achakzai, Kamran Baseer; Shah, Muhammad Abbas; Achakzai, Ramla; Kakar, Ghulam Hussain; Harifal, Muhammad Anwar (Nepalese Journal of Agricultural Sciences, 2025)
A 24-year (1999-2022) retrospective study investigated calf mortality and its causes in Holstein Friesian calves. Divided into eight periods, the data explored how time, season, sire, sex, age and cause of death impacted mortality. Female calves exhibited significant variation (P